Brazil : Issues in Fiscal Federalism - World Bank (Washington, DC, 2013)
The globalization of financial markets, has increased international pressure on the federal governments to maintain a hard budget constraint, with respect to sub-national governments. Because growth in sub-national deficits undermines investor confidence, the federal government is under pressure to enforce the new debt control system, if only to keep the foreign investment flowing, and, political support for enforcement of the fiscal rules may also have increased. Nevertheless, there is the case for shifting the system of sub-national debt control from one that depends on central regulation, to one that relies more on markets. The report looks at institutional models for doing so, which include bond markets, and specialized banks. If the market model is to prevail in Brazil, changes in the credit environment must occur: private long term funds must become available, at interest rates compatible with infrastructure investment returns. But continued macroeconomic stability, and declining federal deficits are required before implementing the market model; private lenders must have a level playing field, and, limitations on subsidized government lending is necessary to attract private sector interest; the federal government should refrain from extending implicit guarantees on private loans to sub-national governments, while establishing a pattern of non-interference in sub-national defaults to private banks; and, reforms should remove obstacles that prevent sub-national governments from becoming creditworthy. Likewise, the growing state pension liabilities challenges the present system of fiscal controls.